Changes in Upper Airway Space in a Patient with Pycnodysostosis Following Primary Surgery and Orthodontic Treatment: A 12-Year Follow-Up Case Report - Edoardo Staderini; Beatrice Castellano; Gioele Gioco; Anna Schiavelli; Davide Gentile (Applied Sciences)
Pycnodysostosis (PDS) is an autosomal recessive form of osteosclerotic skeletal dysplasia characterized by craniofacial anomalies, a high-arched palate, and a narrowed pharyngeal space due to mandibular and maxillary deficiencies. These structural anomalies in the upper airway predispose PDS patients to obstructive sleep apnea (OSA). OSA can be managed in PDS patients using either a conservative (non-surgical and multidisciplinary) approach or surgical interventions. Given the craniofacial anomalies associated with PDS, orthodontic treatment aims to address the maxillary transverse deficit and retrognathia. Currently, there is no evidence regarding the impact of orthodontic therapy on OSA levels among PDS patients. This study reports the long-term morphological and functional changes in the upper airway of a PDS patient following adenotonsillectomy and uvulopalatoplasty at an early age (3.6 years) and orthodontic camouflage in late mixed dentition (10 years). Polysomnographies (PSGs), nuclear magnetic resonance (NMR), and lateral cephalograms taken before and after ENT surgery and orthodontic treatment were analyzed. Lateral X-rays were evaluated for changes in the posterior airway space (PAS), while polysomnographies provided the apnea–hypopnea index (AHI). The NMR scans were segmented to measure the perimeter and radius of the upper airway. The findings of this study indicate that improvements following uvulopalatoplasty (UPP) were partial and temporary. Nonetheless, orthodontic therapy and the use of elastics did not appear to influence the PAS or AHI. Future studies with larger cohorts are needed to evaluate the long-term effectiveness of the UPP procedure. This study was conducted in accordance with the CARE guidelines.